2013
DOI: 10.2139/ssrn.2245672
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Mechanization in Ghana: Is Specialization in Agricultural Mechanization a Viable Business Model?

Abstract: The Government of Ghana (GoG) since 2007 has been providing subsidized agricultural machines to individual farmers and private enterprises established as specialized Agricultural Mechanization Services Enterprise Centers (AMSECs) to offer tractor-hire services to small-scale farmers across the country. Current demand in the country is primarily focused on land preparation services, especially plowing. This paper assesses whether AMSEC enterprises are a viable business model attractive to private investors. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…As a consequence all the farmers sold their bullocks." The decrease of the number of plowboys was also found in a study to animal traction by IFPRI [96]. The census of 2012 [97] confirms that households reported that approximately 91% of school-age children (6 to 15 years) are regularly enrolled in school.…”
Section: Labourmentioning
confidence: 63%
See 1 more Smart Citation
“…As a consequence all the farmers sold their bullocks." The decrease of the number of plowboys was also found in a study to animal traction by IFPRI [96]. The census of 2012 [97] confirms that households reported that approximately 91% of school-age children (6 to 15 years) are regularly enrolled in school.…”
Section: Labourmentioning
confidence: 63%
“…A number of other studies have also captured the increase in mechanized agriculture. A survey conducted by IFPRI in 2013 in four districts of the three northern regions indicates that about 95% of 173 interviewed maize farmers used hired tractor services for land preparation [96]. Data of the Ghana Living Standard Survey 2005/2006 showed that hired labor is the most costly input for farmers, accounting on average for about 50% of total input cost for a farmer in the Northern regions [99].…”
Section: Agricultural Practicesmentioning
confidence: 99%
“…These figures include both own‐farm and hiring‐out operations and are similar to the private enterprises in Ghana (Houssou et al. ).…”
Section: Tractor Owner‐operators In Central Nigeria: Survey and Key Fmentioning
confidence: 99%
“…Among the policies that were put in place was the establishment of Agricultural Mechanization Services Enterprise Centers (AMSECs) to improve smallholder farmers' access to mechanization services. An evaluation of the AMSEC program suggests that it has led to farm expansion among tractor users (Benin et al 2012), but the program is not viable in the medium and long terms unless AMSECs increase their scale of operations (Houssou et al 2013). The Fertilizer Subsidy Program (FSP) is another public spending program that was initiated in 2009, but the program has not been steady to date.…”
Section: Rise To Medium-and Large-scale Farming: the Role Of Policies?mentioning
confidence: 99%